Geologia, petrografia e geocronologia do granito São João, Província Carajás, SSE do Pará - LIMA, Paulo Henrique Araújo (2019)
The São João Granite (SJG) is a subcircular anorogenic batholith with approximately 200km² of area, outcropping between Água Azul do Norte and Bannach cities, southeastern of the Amazonian Craton, Carajás Province. It is intrusive in trondhjemitic and leucogranitic Archean units of the Rio Maria Granite-Greenstone Terrain. The SJG consists mainly of monzogranite and syenogranite isotropic rocks, with pink to reddish colors, poor in mafic minerals, and formed essentially by quartz, alkali feldspar and plagioclase. Amphibole and biotite are the main ferromagnesian minerals, and zircon, apatite, allanite and minerals opaques the dominant accessory phases. The SJG is dominantly medium to coarse-grained, locally fine-grained, outcropping as small hills, big blocks and flooring often fractured. Petrographic studies, based on macroscopic, microscopic and SEM/EDS analysis allowed the identification of four different petrographic facies: amphibole-biotite monzogranite (ABMG), biotite monzogranite (BMG), amphibole-biotite syenogranite (ABSG) and biotite syenogranite (BSG). Among the monzogranite rocks, the BMG is the more abundant facies. These rocks are concentrated in the central west part of the body, with some occurrences in the north and southeast. Rocks of the ABMG facies are widely disperse in the east, southwest and west-central portions of the body. On the other hand, the syenogranite rocks (ABSG and BSG) occur preferentially in the border areas of the pluton, with the BSG rocks being restricted to the western border and the ABSG to the eastern border, with some occurrences in the north and southeast. A representative sample of BMG was selected for dating by the Pb on zircon evaporation method. Among the zircon analyzed crystals, five showed an average age of 1890±2 Ma, interpreted as crystallization age of the SJG. This age is similar to that obtained for the Seringa Granite (1895±1 Ma). Due to petrographic, mineral chemistry (EDS/SEM) and geochronological similarities with rocks of the Seringa Granite, located immediately to the west, and granites of the Serra dos Carajás suite, the São João Granite is included in a first approach, in that important granitoide suite.